The function of the temporomandibular joint and postural balance (тhe state of the question) (LLC "Endo Press", 2020)
Regulation of vertical position is carried out by a set of customizable reflex feedback from the vestibular, visual, joint and muscle receptors. Several studies have shown the importance of a small clinical features of postural disorders balance if disfunkktsii syndrome temporomandibular joint (TMJ). According to others, a minor violation of TMJ function leads to the breakdown of the correctly closing the teeth and accompanied by changes in postural tone. The main method of analysis of the relationship between the occlusal-postural characteristics and clinical symptoms of TMJ is stabilometry.